Hey there! Sign in to join this conversationNew here? Join for free
    • Thread Starter
    Offline

    15
    ReputationRep:
    http://mathsathawthorn.pbworks.com/f/FP1Jun06.pdf
    Can someone help me with 9b?
    • Community Assistant
    • Welcome Squad
    Online

    20
    ReputationRep:
    Community Assistant
    Welcome Squad
    (Original post by English-help)
    http://mathsathawthorn.pbworks.com/f/FP1Jun06.pdf
    Can someone help me with 9b?
    Have you found \frac{dy}{dx} in terms of y and x??

    Now just differentiate both sides again wrt x and multiply both sides by y.
    • Thread Starter
    Offline

    15
    ReputationRep:
    (Original post by RDKGames)
    Have you found \frac{dy}{dx} in terms of y and x??

    Now just differentiate both sides again wrt x and multiply both sides by y.
    Tbh i dont even understand the question , what is it trying to tell me to find out and how should i start?
    • Community Assistant
    • Welcome Squad
    Online

    20
    ReputationRep:
    Community Assistant
    Welcome Squad
    (Original post by English-help)
    Tbh i dont even understand the question , what is it trying to tell me to find out and how should i start?
    Well the first part is asking for a stationary point. Stationary points are found when you set \frac{dy}{dx}=0 for an expression.

    You have y=x^{-x}, \forall x \in \{ \mathbb{R} : x>0 \} and you need to differentiate this. Begin by rewriting this as \ln(y)=\ln(x^{-x})=-x\ln(x) and proceed with implicit differentiation on the LHS for \frac{dy}{dx}
    • Thread Starter
    Offline

    15
    ReputationRep:
    (Original post by RDKGames)
    Well the first part is asking for a stationary point. Stationary points are found when you set \frac{dy}{dx}=0 for an expression.

    You have y=x^{-x}, \forall x \in \{ \mathbb{R} : x>0 \} and you need to differentiate this. Begin by rewriting this as \ln(y)=\ln(x^{-x})=-x\ln(x) and proceed with implicit differentiation on the LHS for \frac{dy}{dx}
    Ive done 9a! :/ I was talking about 9b?
    Sorry , Well i did say 9b in the OP
    http://mathsathawthorn.pbworks.com/f/FP1Jun07.pdf
    I need help on q5^ Basically I have done n=1 and n=k , when i put n=k+1 inside the function , it gives me 2-(k+3)(1/2)^k+1
    Idk what to do next though
    • Community Assistant
    • Welcome Squad
    Online

    20
    ReputationRep:
    Community Assistant
    Welcome Squad
    (Original post by English-help)
    Ive done 9a! :/ I was talking about 9b?
    Sorry , Well i did say 9b in the OP
    http://mathsathawthorn.pbworks.com/f/FP1Jun07.pdf
    I need help on q5^ Basically I have done n=1 and n=k , when i put n=k+1 inside the function , it gives me 2-(k+3)(1/2)^k+1
    Idk what to do next though
    When you said "Tbh i dont even understand the question" I assumed you simply didn't know where to start on the question altogether. For 9b, as I said, just take your \frac{dy}{dx}=-y(1+\ln(x)) and differentiate it again to find \frac{d^2 x}{dy^2}. Then multiply both sides by y of the expression and tidy it up.

    For Q5 if you start your inductive step with  \displaystyle \sum_{r=1}^{k+1} [r\cdot (\frac{1}{2})^r] =2-(k+2)(\frac{1}{2})^k+(k+1)(\frac  {1}{2})^{k+1} and up with 2-(k+3)(\frac{1}{2})^{k+1} then you've basically proved it. You can turn it into 2-[(k+1)+2](\frac{1}{2})^{k+1} for clarity which shows that if the statement is true for n=k then it is true for n=k+1 and you just need to write an ending statement to that.
    • Thread Starter
    Offline

    15
    ReputationRep:
    (Original post by RDKGames)
    When you said "Tbh i dont even understand the question" I assumed you simply didn't know where to start on the question altogether. For 9b, as I said, just take your \frac{dy}{dx}=-y(1+\ln(x)) and differentiate it again to find \frac{d^2 x}{dy^2}. Then multiply both sides by y of the expression and tidy it up.

    For Q5 if you start your inductive step with  \displaystyle \sum_{r=1}^{k+1} [r\cdot (\frac{1}{2})^r] =2-(k+2)(\frac{1}{2})^k+(k+1)(\frac  {1}{2})^{k+1} and up with 2-(k+3)(\frac{1}{2})^{k+1} then you've basically proved it. You can turn it into 2-[(k+1)+2](\frac{1}{2})^{k+1} for clarity which shows that if the statement is true for n=k then it is true for n=k+1 and you just need to write an ending statement to that.
    But do you know , how did you get this step when doing n=k+1 , thats what i dont understand :/
     \displaystyle \sum_{r=1}^{k+1} [r\cdot (\frac{1}{2})^r] =2-(k+2)(\frac{1}{2})^k+(k+1)(\frac  {1}{2})^{k+1}
    • Community Assistant
    • Welcome Squad
    Online

    20
    ReputationRep:
    Community Assistant
    Welcome Squad
    (Original post by English-help)
    But do you know , how did you get this step when doing n=k+1 , thats what i dont understand :/
     \displaystyle \sum_{r=1}^{k+1} [r\cdot (\frac{1}{2})^r] =2-(k+2)(\frac{1}{2})^k+(k+1)(\frac  {1}{2})^{k+1}
    Right so when you do it for n=1 it works out.

    Now assume it works for n=k therefore out inductive assumption is that \displaystyle \sum_{r=1}^{k} [r\cdot (\frac{1}{2})^r] =2-(k+2)(\frac{1}{2})^k

    Next we must test it for n=k+1

    So we have \displaystyle \sum_{r=1}^{k+1} [r\cdot (\frac{1}{2})^r] = \sum_{r=1}^{k} [r\cdot (\frac{1}{2})^r] + \underbrace{(k+1)(\frac{1}{2})^{  k+1}}_{(k+1)^{th} \text{term}} = \underbrace{2-(k+2)(\frac{1}{2})^k}_{\text{ inductive assumption}} + (k+1)(\frac{1}{2})^{k+1}
    • Thread Starter
    Offline

    15
    ReputationRep:
    (Original post by RDKGames)
    Right so when you do it for n=1 it works out.

    Now assume it works for n=k therefore out inductive assumption is that \displaystyle \sum_{r=1}^{k} [r\cdot (\frac{1}{2})^r] =2-(k+2)(\frac{1}{2})^k

    Next we must test it for n=k+1

    So we have \displaystyle \sum_{r=1}^{k+1} [r\cdot (\frac{1}{2})^r] = \sum_{r=1}^{k} [r\cdot (\frac{1}{2})^r] + \underbrace{(k+1)(\frac{1}{2})^{  k+1}}_{(k+1)^{th} \text{term}} = \underbrace{2-(k+2)(\frac{1}{2})^k}_{\text{ inductive assumption}} + (k+1)(\frac{1}{2})^{k+1}
    So you get the get the Inductive assumption from n=k and then do n=k=1 which comes from the LHS? + then add both of them?
    • Community Assistant
    • Welcome Squad
    Online

    20
    ReputationRep:
    Community Assistant
    Welcome Squad
    (Original post by English-help)
    So you get the get the Inductive assumption from n=k
    Yes we need to establish an assumption before we can proceed with the proof.

    and then do n=k+1 which comes from the LHS? + then add both of them?
    You test for n=k+1 and to do so you need to make use of the assumption you made earlier. The only way to do this is to split the sum from r=1 to r=k+1 into 2 different terms where one can be replaced by the assumption (the one which goes from r=1 to r=k) and the other is whatever is left over to balance the sum (the (k+1)th term). So then you just add the two things and should end up with an expression for n=k+1
    Offline

    3
    ReputationRep:
    (Original post by English-help)
    So you get the get the Inductive assumption from n=k and then do n=k=1 which comes from the LHS? + then add both of them?
    To add to what RDK games has said, the whole structure of a proof by induction is to make some use of your assumption in the inductive step - that's where the real power of this type of proof comes from.

    In this case, you have assumed that  \displaystyle\sum_{r=1}^k \left( \left(\frac{1}{2}\right)^r r\right) = 2 - \displaystyle \left(k+2\right)\left(\frac{1}{2  } \right)^{k} .

    So a nice way in which we can use our assumption here is if we partition the sum in our inductive step:

     \displaystyle\sum_{r=1}^{k+1} \left( \left(\frac{1}{2}\right)^r r\right) =  \displaystyle\sum_{r=1}^k \left( \left(\frac{1}{2}\right)^r r\right) + \text{the }(k+1)^{\text{th}} \text{ term} ,

    which allows us to use the assumption by just substitution.
    • Thread Starter
    Offline

    15
    ReputationRep:
    (Original post by crashMATHS)
    To add to what RDK games has said, the whole structure of a proof by induction is to make some use of your assumption in the inductive step - that's where the real power of this type of proof comes from.

    In this case, you have assumed that  \displaystyle\sum_{r=1}^k \left( \left(\frac{1}{2}\right)^r r\right) = 2 - \displaystyle \left(k+2\right)\left(\frac{1}{2  } \right)^{k} .

    So a nice way in which we can use our assumption here is if we partition the sum in our inductive step:

     \displaystyle\sum_{r=1}^{k+1} \left( \left(\frac{1}{2}\right)^r r\right) =  \displaystyle\sum_{r=1}^k \left( \left(\frac{1}{2}\right)^r r\right) + \text{the }(k+1)^{\text{th}} \text{ term} ,

    which allows us to use the assumption by just substitution.
    So you get the K+1 term when you put k+1 into the left hand side basically and the K term from when you do n=k? right?
    Offline

    3
    ReputationRep:
    (Original post by English-help)
    So you get the K+1 term when you put k+1 into the left hand side basically and the K term from when you do n=k? right?
    Yes, if I understand what you're saying correctly
    • Thread Starter
    Offline

    15
    ReputationRep:
    (Original post by crashMATHS)
    Yes, if I understand what you're saying correctly
    Thank you

    Posted from TSR Mobile
 
 
 
  • See more of what you like on The Student Room

    You can personalise what you see on TSR. Tell us a little about yourself to get started.

  • Poll
    Would you like to hibernate through the winter months?
    Useful resources

    Make your revision easier

    Maths

    Maths Forum posting guidelines

    Not sure where to post? Read the updated guidelines here

    Equations

    How to use LaTex

    Writing equations the easy way

    Student revising

    Study habits of A* students

    Top tips from students who have already aced their exams

    Study Planner

    Create your own Study Planner

    Never miss a deadline again

    Polling station sign

    Thinking about a maths degree?

    Chat with other maths applicants

    Can you help? Study help unanswered threads

    Groups associated with this forum:

    View associated groups
  • See more of what you like on The Student Room

    You can personalise what you see on TSR. Tell us a little about yourself to get started.

  • The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

    Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE

    Quick reply
    Reputation gems: You get these gems as you gain rep from other members for making good contributions and giving helpful advice.